Topological Properties of Degree-Based Invariants via M-Polynomial Approach - Samirah Alsulami; Sabir Hussain; Farkhanda Afzal; Mohammad Reza Farahani; Deeba Afzal (Journal of Mathematics)
Chemical graph theory provides a link between molecular properties and a molecular graph. The M-polynomial is emerging as an efficient tool to recover the degree-based topological indices in chemical graph theory. In this work, we give the closed formulas of redefined first and second Zagreb indices, modified first Zagreb index, nano-Zagreb index, second hyper-Zagreb index, Randić index, reciprocal Randić index, first Gourava index, and product connectivity Gourava index via M-polynomial. We also present the M-polynomial of silicate network and then closed formulas of topological indices are applied on the silicate network.